2020
DOI: 10.22159/ijap.2020v12i3.34358
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simplex Lattice Design in Development of Oral Self-Nanoemulsifying Drug Delivery System Containing Rosuvastatin Calcium

Abstract: Objective: The aim of the present work was to enhance the solubility of rosuvastatin calcium by self-nano emulsifying drug delivery system (SNEDDS) using mixtures of oil, cosolvent, surfactant and cosurfactant. Methods: Based on solubility study and emulsification efficiency, Preliminary investigations of various oils, surfactants and cosurfactants were carried out for the selection of the proper SNEDDS ingredients. Pseudo-ternary phase diagrams were constructed to identify the efficient self-emulsificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
1
2
0
8
Order By: Relevance
“…A pseudo ternary phase diagram was created to identify efficient self-emulsification regions. In vitro diffusion studies revealed that the release of calcium rosuvastatin from SNEDDS was faster [28].…”
Section: Verification Of Optimal Snedds Formula Combination Of Mfgmentioning
confidence: 99%
“…A pseudo ternary phase diagram was created to identify efficient self-emulsification regions. In vitro diffusion studies revealed that the release of calcium rosuvastatin from SNEDDS was faster [28].…”
Section: Verification Of Optimal Snedds Formula Combination Of Mfgmentioning
confidence: 99%
“…Beberapa fase minyak yang digunakan dalam formulasi SNEDDS meliputi capryol PGMC, minyak biji jintan hitam, asam oleat, minyak kelapa/VCO, capryol-90, olive oil, capryol-90, peceol, kombinasi peceol dan etiloleat, capmul MCM dan cremophor EL. [5][6][7][8][9][10][11]14,22,23 Suatu Surfaktan dapat menghasilkan nanoemulsi tipe minyak dalam air apabila memiliki HLB>10. 24 Surfaktan yang terlokalisasi pada droplet emulsi dapat menurunkan energi bebas antar muka dan menghasilkan barier terhadap koalesensi sehingga terjadi dispersi spontan secara termodinamika.…”
Section: Sneddsunclassified
“…25 kombinasi tween 20:labrasol (1:1), cremophor EL, cremophor 40, tween 20, labrasol, cremophor EL 300 dan acrysol K 140. [5][6][7][8][9][10][11]14 Ko-surfaktan berfungsi untuk meningkatkan fluiditas antar muka dengan cara penetrasi ke dalam film surfaktan. 13 Pemilihan fase minyak pada SNEDDS didasarkan pada kelarutan maksimal zat aktif dalam fase minyak, sedangkan pemilihan surfaktan dan ko-surfaktan berdasarkan pada kelarutan maksimum obat dalam surfaktan dan kosurfaktan serta efisiensi emulsifikasi terhadap fase minyak.…”
Section: Sneddsunclassified
See 2 more Smart Citations